Distribusi Vaksin yang Berkeadilan: Kajian Bioetika pada Isu Penolakan Vaksin di Era Modern - Nurin Fatnata; Virna Fianarita Rahmawati; Tri Cahyanto (Jurnal Cakrawala Pendidikan dan Biologi, 2026)
Equitable vaccine distribution is a global issue that has received increasing attention, especially since the increasing need for vaccines in the face of modern pandemics. This study aims to analyze the inequality in vaccine distribution and the factors influencing vaccine hesitancy through a descriptive qualitative approach, utilizing literature studies and supporting data in the form of graphs. The analysis results show that high-income countries have significantly greater access to vaccines than middle- and low-income countries, creating inequalities that impact public health protection. Furthermore, levels of vaccine hesitancy were found to vary across social groups, with adolescents being the group with the highest rate of rejection due to the influence of misinformation and low trust in health institutions. These findings confirm that the success of a vaccination program is determined not only by the availability of equitable distribution but also by public acceptance, which is influenced by social, psychological, and ethical factors. Overall, this study emphasizes the importance of applying bioethical principles such as justice, beneficence, and autonomy in formulating effective and inclusive vaccination policies.